Clima organizacional y el desempeño laboral de los trabajadores del Consorcio La Arena S.A.C. - Benites Marquina, Ikoll Joseph (2012)
This work correlational descriptive research, aims to determine if the weather directly affects organizational performance level workers Consorcio La Arena. Consorcio La Arena S.A.C. is a company that provides procurement and personnel allocation (job placement), provides unskilled labor, which is distributed in different areas among which: Geology Exploration, Environment, camps cleaning, laundry, kitchen, under guardianship requirement of our customers, these activities are supervised by the staff of the consortium. In response to the statement of the problem, the sample universe, consisting of 55 people, they were given interviews, observation guides, polls and performance evaluation during the month of August 2012. According to the results, regarding the organizational climate of scored 160.5 points, compared to 65.3 points performance was obtained, both values reflect average levels in the corresponding scale and also yielded a Pearson correlation coefficient of 0.8706 which refers that there is a direct influence of organizational climate on the level of worker performance Consorcio La Arena.